2009
DOI: 10.2139/ssrn.1368756
|View full text |Cite
|
Sign up to set email alerts
|

Tribal Social Instincts and the Cultural Evolution of Institutions to Solve Collective Action Problems

Abstract: Human social life is uniquely complex and diverse. Much of that complexity and diversity arises from culturally transmitted ideas, values and skills that underpin the operation of social norms and institutions that structure our social life. Considerable theoretical and empirical work has been devoted to the role of cultural evolutionary processes in the evolution of social norms and institutions. The most persistent controversy has been over the role of cultural group selection and geneculture coevolution in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 131 publications
0
58
0
4
Order By: Relevance
“…The goal of the model is to understand under what conditions ultrasocial norms and institutions will spread. The theoretical framework is provided by CMLS (5,17). As explained previously, withingroup forces cause ultrasocial traits to collapse and to be replaced with noncooperative traits.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of the model is to understand under what conditions ultrasocial norms and institutions will spread. The theoretical framework is provided by CMLS (5,17). As explained previously, withingroup forces cause ultrasocial traits to collapse and to be replaced with noncooperative traits.…”
Section: Methodsmentioning
confidence: 99%
“…Our theoretical framework for understanding the evolution of social norms and institutions is provided by cultural multilevel selection (CMLS) (5,17). Because the benefits of ultrasocial institutions are only felt at larger scales of social organization, and costs are born by lower-level units, fragmentation into lowerlevel units often leads to a loss of such institutions.…”
Section: Ultrasocial Norms and Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We stress that the institution comprises the negotiation process as well as the resulting norms or rules of behaviour [11, p. 128]. This is in contrast to the cultural evolution literature, which equates institutions with equilibrium norms of behaviour in an economic game form [20], rather than with a political game form that generates rules for the economic game form.…”
Section: Institutions (A) What Is An Institution?mentioning
confidence: 99%
“…The study of cultural evolution seeks to explain the diversity of human behavior observed worldwide and offers a mechanistic, causal framework for understanding changes in socially learned norms, values, and institutions (Richerson and Boyd 2005). It draws heavily from the diffusion of innovations literature (Richerson and Boyd 2005) and is complementarity with psychology (Mesoudi 2009), economics (van den Bergh andGowdy 2000;Bowles 2004;Hodgson and Knudsen 2010;Safarzyńska 2013), and organizational theory (Hodgson 2013), among other frameworks (Gintis 2007).…”
Section: Applying Cultural Evolution To Sustainability Challengesmentioning
confidence: 99%